A bibliometric analysis of Balanced Scorecard research with higher education by VOSviewer - LiangYan, M.A.; Ali, Mass Hareeza; Mohd Said, Ridzwana (Elite Scientific Publications, 2024)
This paper reviews the research advancements related to the Balanced Scorecard through a bibliometric analysis using VOSviewer in the context of higher education. It introduces the background and evolution of the Balanced Scorecard, elaborating on its applications and key factors within higher education. This study examines country collaboration and keyword co-occurrence across 259 articles on the Balanced Scorecard in higher education by VOSviewer, sourced from the SCOPUS database spanning from 1997 to 2024. The findings indicate that research in this domain has been continuous since the inception of the theory. The United States and the United Kingdom emerged as early leaders in the field, while China and Iran entered the research landscape later, with an average starting year of 2018. The keyword co-occurrence analysis reveals that, alongside the evolution of the Balanced Scorecard theory, there has been increasing research interest in performance management and strategic management within higher education. Despite Kaplan & McMillan introducing the concept of the triple bottom line of the Balanced Scorecard—comprising social, economic, and environmental value—in 2020, there remains a lack of relevant research in higher education.